Assessing the Knowledge on Safety Handling of Contact Lens among Students, Cyberjaya, Selangor, Malaysia - Walaa Wahid Abdullah Wajih; Mohamad Syakir Zainuddin; Qadijaah Azami; Ameer Ikhwan Azminudin; Sathappan Subramaniam (Asian Journal of Medicine & Health Sciences, 2022)
Introduction: Contact lenses have been used for refractive error correction or cosmetic purposes and have been increasingly popular worldwide. However, careless contact lens use poses a risk of developing complications like polymicrobial keratitis, contact lens related corneal ulcer, acanthamoeba keratitis and dry eyes. Method: Utilizing an online questionnaire, a cross-sectional study was conducted among 182 University of Cyberjaya (UOC) students to determine their knowledge level, their compliance rate concerning the proper handling of contact lenses and the association between them. The questionnaire used was a self-explained structured set of questions which was pretested and revised by two ophthalmologists in the Faculty of Medicine. Results: Participating in the survey were 75% female and 25% male; 57% of participants had unsatisfactory knowledge, with no significant difference in knowledge between contact lens wearers and non-wearers. Only 37% of those who were compliant had satisfactory knowledge and there was no association between knowledge and compliance among contact lens wearers. Conclusion: In this study found there was no significant association between knowledge and compliance to proper contact lens handling among contact lens wearers. Therefore, it is recommended an awareness program be conducted to promote healthy contact lens care and wear among students.